Psychological and Social Alienation in the Autobiographical Novel I Saw Ramallah by Mourid Barghouthi - Barazane, Nadia; Khaloui, Choumayssa (Arts for Linguistic & Literary Studies, 2025)
This study investigates psychological and social alienation in Mourid Barghouthi’s autobiographical novel I Saw Ramallah, portraying exile as a transformative experience that reshapes the Palestinian self both emotionally and socially. Employing sociological and psychological frameworks, the research traces the protagonist’s return after decades of displacement, revealing that repatriation does not dissolve alienation but amplifies it, as the reality of the homeland diverges sharply from its imagined image. The novel captures the complex interplay between personal estrangement and collective dislocation, reflecting the fragmentation of a people suspended between a lost homeland, a substitute exile, a conditional return, and an evolving identity. It further illustrates how language functions as a mirror of alienation, encapsulating the tension between memory and present reality. Through its narrative, I Saw Ramallah underscores the existential rupture experienced by the exiled Palestinian under the weight of political oppression and fluid social contexts, demonstrating that the end of physical exile often marks the beginning of a deeper, more profound estrangement.